Empreendedorismo digital sob a ótica das capacidades dinâmicas: proposição de framework de elementos de análise para organizações - Pinto, Alexandre Rodrigues (2024)
The phenomenon of entrepreneurship is essentially the pursuit of opportunities, focusing on recognizing and transforming them into marketable goods or services, taking risks, and generating results. In the academic context, entrepreneurship has been studied to understand how opportunities are discovered and exploited, impacting the economic development of organizations. In recent years, the rapid technological evolution and integration of digital systems have enabled the emergence of digital entrepreneurship, which combines entrepreneurship with digital technologies, creating a vast range of possibilities and widely impacting organizations. This type of entrepreneurship, which stands out in the global economy and academic studies, is the focus of this research. It involves the creation and design of products or services in a digital environment, leveraging Internet and mobile technologies, facilitating the exchange and acquisition of knowledge, and enabling new forms of business, heavily influenced by digitalization and artificial intelligence. This doctoral thesis offers a contribution to the understanding and application of digital entrepreneurship in the organizational context, from the perspective of dynamic capabilities. Dynamic capabilities are essential in the context of digital entrepreneurship, as they allow organizations to develop, integrate, and reconfigure resources and competencies in response to rapid changes in the technological environment, thereby ensuring their competitiveness and sustainability in the digital market. By integrating three distinct studies, it was possible to develop a framework that analyzes and guides the understanding of digital entrepreneurship in organizations within a technologically evolving business environment. The framework, based on dynamic capabilities, allows for the analysis of digital entrepreneurship by observing elements identified in the literature and organizational practices. The first study identified, through an integrative literature review, 56 elements of digital entrepreneurship analysis, grouped into 12 categories and four macro categories, based on dynamic capabilities. The second study refined the framework based on expert experience, through in-depth interviews, constructing and refining the framework based on emerging elements from practice and insights from professionals and academics. The third study examined the applicability of the framework through in-depth interviews with experts (entrepreneurs and employees of organizations engaged in digital entrepreneurship). The results demonstrate that digital entrepreneurship is constantly evolving, highlighting the importance of dynamic capabilities in agile and highly mutable environments. The developed framework provides a theoretical and practical structure with 28 elements organized according to the theory of dynamic capabilities, divided into four macro categories and nine categories to analyze digital entrepreneurship in organizations. This allows for its analysis from the perspective of dynamic capabilities by observing how these capabilities enable continuous adaptation, innovation, and the exploration of new opportunities in a volatile business environment, making the creation of sustainable competitive advantages possible. The practical contributions of this study include valuable insights into how organizations can adapt and thrive in digitalized environments, integrating and reconfiguring their competencies to face challenges and seize opportunities in the digital market. This framework may be useful for researchers, academics, and professionals, promoting a deeper understanding and accurate analysis of digital entrepreneurship, consolidating its role as a driver of innovation and economic growth.